Advances in targeting protein S-palmitoylation in tumor immunity and therapy - Han, Miaomiao; Lv, Yuanhao; Chen, Yiyang; Li, Zhaoyi; Tian, Jiaqi; Zhou, Hongyan; Wang, Yunlong; Su, Wei; Zhong, Jiateng (Frontiers in Oncology, 2025)
S-palmitoylation is a reversible and dynamic post-translational modification of proteins. A palmitoyl group is covalently attached to a cysteine residue of the protein by a thioester link. It regulates the transcription and expression of downstream target genes and cell signaling, influencing cellular functions. Research indicates a substantial correlation between S-palmitoylation and tumorigenesis and immunotherapy, where it plays a pivotal role in modulating T cell activation, cytokine signaling, autophagy, phagocytosis, and death. Moreover, palmitoylation contributes to drug resistance and immunological evasion in tumor cells, enabling them to circumvent the effects of chemotherapeutic drugs and immune surveillance. Inhibitors that target S-palmitoylation have demonstrated significant potential in enhancing the efficacy of tumor immunotherapy, offering a novel strategy for cancer treatment. Nonetheless, obstacles such as inhibitor specificity and efficacy persist, requiring more extensive investigations into the exact mechanisms of S-palmitoylation to develop more effective targeted therapeutics. This article summarizes recent developments in S-palmitoylation concerning tumor immunity and treatment. The article examines the regulatory function of S-palmitoylation, its modifying enzymes in tumor cell signaling, and novel tumor immunotherapies that target S-palmitoylation.